High-temperature behavior of structural and non-structural shotcretes. (October 2016) - Bamonte, Patrick; Gambarova, Pietro G.; Nafarieh, Alireza
Abstract: Sprayed concrete (shotcrete) is well known as a reliable and effective material for rock stabilization, fire proofing of metallic structures and jacketing of R/C members. Shotcrete structural applications, however, have been so far very limited mainly because of some concerns about material's durability and high-temperature behavior. The latter issue is the starting point of this research project aimed to investigate the thermo-mechanical properties of three shotcretes containing different accelerating agents (based on sodium silicates in one mix – C1, and on sulfo-aluminates in two mixes – C2/C2F, no steel fibers/with steel fibers). The objective is to check (a) whether the heat-triggered mechanical decay of shotcrete is similar to that of ordinary concrete, and (b) how shotcrete low thermal diffusivity and relatively large porosity evolve at high temperature. The mechanical properties in compression are investigated both at high temperature (hot tests, C2 and C2F) and past cooling (residual tests, all mixes). In terms of normalized mechanical decay, the two shotcretes containing an alkali-free accelerating agent behave similarly to ordinary concrete, while the shotcrete with an alkaline accelerating agent is more heat and age sensitive. Up to 850 °C, all mixes exhibit a markedly lower thermal diffusivity compared with ordinary concrete, and a higher porosity. Furthermore, the rather low mechanical properties of the shotcrete with an alkaline accelerator with respect to the base material make it hardly fit for structural purposes, while the two shotcretes with an alkali-free accelerator are as good as any ordinary concrete even at high temperature, as demonstrated by the basic structural application presented at the end of the paper, concerning the lining of a circular deep R/C tunnel exposed to the standard fire.